(untitled) (Journal of the College of Education for Women, 2019)
The research deals with financial and supplies support from the rulers and governors of theArab cities and Islamic regions to the poor of common people and the poor of their own . TheIslamic Arab community was characterized , since the prophet’s era , with great humanisticfeatures that formed the cultural characteristic which organized individual’s economic life .The prophet , senior Muslims and the rich cared a lot about this side . There was a largevariation in the degrees of wealth and poverty in the Muslim Arab community as a heritagefrom the pve – Islamic society where there is no concern about helping the needy and poor .Thus , the research sheds light on the different forms of help offered by rulers and governersto the poor especially during the Rashidi and Umayyad eras